1998
DOI: 10.1016/s0735-1097(98)00142-9
|View full text |Cite
|
Sign up to set email alerts
|

Underestimation of Extent and Severity of Coronary Artery Disease by Dipyridamole Stress Thallium-201 Single-Photon Emission Computed Tomographic Myocardial Perfusion Imaging in Patients Taking Antianginal Drugs

Abstract: Continued use of antianginal drugs before dipyridamole plus low level treadmill exercise thallium-201 SPECT may reduce the extent and severity of myocardial perfusion defects, resulting in underestimation of coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 37 publications
3
32
1
Order By: Relevance
“…This observation is in agreement with a previous report demonstrating that b-blockade with metoprolol decreases the sensitivity of dipyridamole MPI for the detection of individual stenosis by 24% (4). Altogether, these results confirm earlier observations suggesting that antianginal drugs might adversely affect the diagnostic accuracy of vasodilator imaging (5,6,12). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation is in agreement with a previous report demonstrating that b-blockade with metoprolol decreases the sensitivity of dipyridamole MPI for the detection of individual stenosis by 24% (4). Altogether, these results confirm earlier observations suggesting that antianginal drugs might adversely affect the diagnostic accuracy of vasodilator imaging (5,6,12). …”
Section: Discussionsupporting
confidence: 90%
“…Until recently, it was thought that b-blockers had no effect on the action of primary coronary vasodilators (1). However, studies with dipyridamole have challenged this view (4,5). Treatment with a b 1 -adrenoceptor blocker attenuated the coronary hyperemic response to dipyridamole as measured by 13 N-ammonia PET (6) and reduced the magnitude of inducible perfusion abnormalities on dipyridamole MPI (4).…”
mentioning
confidence: 99%
“…In addition, adenosine increased the median heart rate to 69 beats per minute (interquartile range, 60-78 beats per minute), potentially increasing motion artifacts that may be mistaken for perfusion abnormalities. Recognizing these issues, we prespecified a SSS threshold of at in general, antianginal drugs reduce ischemic burden at SPECT (25). Sharir et al (25) previously demonstrated that antianginal drugs reduce myocardial ischemia most effectively in the territory of the left anterior descending and left circumflex arteries, with no significant reduction in the territory of the right coronary artery.…”
Section: Disclosures Of Conflicts Of Interest: Rtgmentioning
confidence: 99%
“…Indirect evidence indicating the potential use of stress myocardial perfusion scintigraphy in evaluating the efficacy of anti-ischemic drugs originated from studies reporting underestimation of the extent and severity of myocardial ischemia in patients submitted to pharmacological stress myocardial perfusion imaging under the effect of previous intravenous propranolol injection [34] or nondiscontinuation of routine anti-ischemic drugs [35].…”
Section: Serial Assessment Of Extent and Severity Of Myocardial Ischemiamentioning
confidence: 99%